Pengaruh Perceived Ease of Use dan Perceived Usefulness dalam Teknologi Informasi Terhadap Attitude Toward Using Klampid New Generation (KNG) di Dinas Kependudukan dan Pencatatan Sipil Kota Surabaya - Endriati, Gusti Nana; Untarini, Nindria (Seminar Nasional Manajemen, 2025)
This research is motivated by the phenomenon of information technology utilization at the Department of Population and Civil Registration of Surabaya City, which represents a new form of adaptation for Surabaya residents in managing population administration. Previously, residents were accustomed to submitting applications manually or offline by visiting the office and meeting directly with officers. However, they are now directed to use a technological innovation called Klampid New Generation (KNG), which allows them to submit applications independently online. This study aims to determine the influence of two factors perceived ease of use and perceived usefulness on attitude toward using the KNG information technology. This research employs a survey method with quantitative analysis, using a sample of 110 respondents who are residents of Surabaya aged 17–60 years and have used KNG in their population administration processes. Data were collected through the distribution of questionnaires and analyzed using multiple regression analysis. The results of this study show that (1) Perceived ease of use has a positive and significant effect on attitude toward using KNG, (2) Perceived usefulness has a positive and significant effect on attitude toward using KNG.